How Does the Visibility of LGBTQ+ Directors Influence Firm Value? The Mediating Role of Environmental, Social, and Governance Performance - Federo, Ryan; Aguilera, Ruth V. (Human Resource Management, 2025)
ABSTRACTBoard directors who identify as lesbian, gay, bisexual, transgender, queer, and other identities (LGBTQ+) are now more visible at the corporate apex, as the attainment of diversity, equity, and inclusion at the upper echelons is a goal for many organizations, researchers, and policymakers worldwide. The visibility of LGBTQ+ directors implies the shift toward truly diverse boards that demonstrate commitment to the provision of equal career opportunities and empowerment for all types of individuals. However, we still lack knowledge regarding the relationship between LGBTQ+ board representation and firm outcomes. Drawing on upper echelons and signaling theories, we examine a sample of Fortune 500 companies to identify how LGBTQ+ directors influence their firm values. Our OLS regressions on an unbalanced panel dataset of 441 firms in 2021–2022 reveal that the visibility of LGBTQ+ directors is positively associated with enterprise value, and this relationship is mediated by environmental, social, and governance performance, which can be attributed to corporate social performance. Our research contributes to the literature by showing how the visibility of LGBTQ+ status in the boardroom can matter on firms.